The Prognostic and Predictive Significance of circRNA CDR1as in Tumor Progression - Jian, Fang; Yangyang, Ren; Wei, Xu; Jiadan, Xu; Na, Li; Peng, Yang; Maohong, Bian; Guoping, Niu; Zhaoji, Pan (Frontiers in Oncology, 2021)
Cerebellar degeneration-related protein 1 antisense (CDR1as) is an important member of the circRNAs family, also known as cirs-7. Its main function in vivo is to act as a mir-7 sponge. Accumulated studies show that CDR1as is closely related to various diseases, especially cancer. Our analysis show that CDR1as expression in human cancer is significantly associated with poor overall survival (hazard ratio [HR]=2.50, 95% confidence interval [CI]=2.06–3.04; p<0.00001), and that high CDR1as expression is associated with the tumor node metastasis stage (odds ratio [OR]=2.13, 95% CI=1.63–2.78; p< 0.00001), and distant metastasis (OR=3.50, 95% CI=1.90–6.64; p<0.00001). Furthermore, the results reveal the prognostic significance of CDR1as in neoplasms of the digestive system (HR=1.69, 95% CI=2.14–2.71; p<0.001), colorectal cancer (HR=1.34, 95% CI=1.96–2.85; p<0.001), and non-small cell lung cancer (HR=2.40, 95% CI= 3.42–4.83; p=0.008). In this study, we summarize in detail the latest research findings and demonstrate the function and regulatory mechanism of CDR1as in various cancer processes, and its potential as a biomarker for cancer prevention and prognosis.